Influence of Rubber Crumbs on the Structural Efficiency of Concrete Made from Ceramic Tile Aggregates - Adetiloye, A.; Akinyele, J. O.; Adeoye, O. W.; Labiran, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The indiscriminate dumping of used tyres and construction waste like ceramic tiles has contributed to the present unclean environment. As part of the efforts in the recycling of these waste materials, they were both introduced to concrete, and the effect of these two materials on the structural properties of concrete was studied in this work. Crushed ceramic tiles were used to totally replace granite as the coarse aggregate, while crushed tyre rubber crumbs replaced sand as fine aggregate (0%, 5% and 10%), designated as C0, C5 and C10 respectively. The mix ratio was 1:2:2 for cement, fine and coarse aggregates at 0.5 water/cement ratio, concrete was cured for 7 and 28 days. 100 x 100 x 100 mm concrete cubes were used for the compressive and 100 x 100 x 750 mm beam was used for the flexural strength tests. The results obtained from both compressive and flexural tests showed a general reduction in strength, this was due to the ceramic tiles that absorbed excess water into the concrete. The ACI 209R-92 equations for the prediction of concrete strength were used to determine the one-year strength of the concrete samples. Statistical analysis showed that the R2 of the strength within one year was 0.83 and 0.77 for the C0 and C5 samples respectively. The presence of rubber crumbs served as fillers, especially in the C5 samples. It was concluded that crushed ceramic tiles and rubber crumbs could be used in structural concrete, but should not exceed 5% of rubber crumbs.